Enhancing Human Capital at Scale - Francesco Agostinelli; Ciro Avitabile; Matteo Bobba (Institute of Labor Economics (IZA), 2021)
A two-year randomized evaluation shows that the effectiveness of multi-tasking men- tors on schooling outcomes crucially depends on their training. While a standard training modality in highly marginalized communities in Mexico generates null results, enhanced training yields sizable treatment effects on primary school children's cognitive, behavioral, and educational achievements. This difference cannot be explained by remedial educational activities or pedagogical support, but it can be reconciled with higher parental aspirations and investments. Evidence gathered on the subsequent national roll out of the intervention with enhanced training substantiates the external validity of our findings.
Keywords: H43; I10; I20; I38; 330; pedagogical practices; remedial education; family investments; educational investments; scaling-up effects